Administrative and Legal Means of Ensuring State Information Security in Wartime (Bulletin of Kharkiv National University of Internal Affairs, 2025)
This article is devoted to the analysis of administrative and legal means of ensuring state information security in a state of martial law, particularly in the context of the current Russian-Ukrainian war. It examines the theoretical foundations of information security, key threats, organisational and legal mechanisms and means of their implementation aimed at protecting the national information space.It is noted that the relevance of the topic is due to the escalation of hybrid threats, where the information component plays a decisive role in ensuring national security and social stability. The theoretical foundations are based on the principles of confidentiality, integrity and availability of information (CIA model), adapted to wartime conditions, with integration into the national security system in accordance with the Law of Ukraine “On National Security of Ukraine”.The concepts of information warfare and resilience are considered, which include multi-level protection – from the individual to the state level. A review of scientific research demonstrates the evolution of approaches from theoretical concepts to practical recommendations.It is stated that threats to information security in 2025 include disinformation, propaganda, cyberattacks (DDoS, phishing, interference with critical infrastructure), as well as internal vulnerabilities such as low information culture and data leaks. Particular attention is paid to the latest cyber threats, including attacks using artificial intelligence, social engineering, and attacks on supply chains, which complicate the protection of critical infrastructure.It is emphasised that organisational and legal mechanisms cover the activities of the National Security and Defence Council of Ukraine, the State Service for Special Communications and Information Protection of Ukraine, the Security Service of Ukraine, as well as the regulatory and legal framework, including the Constitution of Ukraine, the relevant regulatory and legal framework, and the Decree of the President of Ukraine “On the Introduction of Martial Law in Ukraine” dated 24 February 2022 No. 64/2022. Measures are divided into administrative (media licensing, telethon), legal (criminal and administrative liability), technical (cyber protection, encryption, data backup) and social (media literacy, strategic communications). The Law of Ukraine “On Amendments to Certain Laws of Ukraine on Information Protection and Cyber Protection of State Information Resources and Critical Information Infrastructure” dated 27 March 2025 No. 4336-IX strengthens protection through standardisation and the creation of a national cyber incident response system.It is concluded that administrative and legal measures are a key element of national defence, but need to be improved through enhanced coordination, practical implementation and international cooperation with the EU and NATO. Relevant recommendations have been made, namely: the adoption of a special law, the creation of a single centre to counter disinformation, the development of cyber technologies, the conduct of regular media literacy training for the population, and the introduction of effectiveness audits. The need for a comprehensive approach to ensure the resilience of the information space by 2026 was emphasised, given the predicted growth of threats from artificial intelligence and cyberattacks.